Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Di SDN 035 Soka Kota Bandung - Nurhayati, Elis; Afriani, Dessy (Peneliti.net, 2024)
The Pancasila learner profile is designed to answer one big question, namely students with what kind of profile (competence) the Indonesian education system wants to produce. So that with the launch of the Pancasila Learner Profile Strengthening Project (P5) program, it is hoped that Indonesian students will have the competence to become democratic citizens and become superior and productive humans in the 21st century. As a driving school, SDN 035 Soka, Bandung City was entrusted to first implement the Merdeka Curriculum, where P5 is part of its implementation. How the implementation of P5 at SDN 035 Soka is detailed and what steps have been taken is an interesting thing to research and learn. The research used a qualitative method with a descriptive approach, where data collection techniques were carried out through interviews about P5 activities to teachers and students. The results obtained that SDN 035 Soka Bandung City has implemented P5 well and should be a model for other schools, especially at the elementary school level and equivalent.